Leadership Model of Pastor and Presbyter in Church Stewardship - Pairikas, Fenetson; Tari*, Ezra; Luji, Daud Saleh (Universitas Syiah Kuala, 2024)
The goal of this article is to demonstrate the significance of pastors and presbyters working together to lead the church. This is due to a lack of them having to create healthy relationships and support one another. The research method used was qualitative. According to the findings of the study, pastors and presbyters have a role as pastors who care for congregation members. They must maintain relationships with the congregation, answer questions, offer support, and shepherd the congregation in their spiritual journey. The pastor is responsible for the worship service, preaching God's Word, and leading the congregation in prayer. Meanwhile, the presbyter has responsibility for handling church funds, creating church policies, and helping make key decisions. Pastors and presbyters collaborate to guide the church in carrying out its spiritual and administrative missions. They must have a positive working connection, support one another, and understand one another's roles. This contributes to the formation of a healthy and successful church in ministry.